Enhancement of the marketing strategies of the Quezon City Public Library - Almenario, Krizia Shae B. (2012)
Marketing the library's services and products is an important aspect in a library's growth. This study focused on enhancing the current marketing strategies of the Quezon City Public Library's (QCPL) services and collections to its community. The study is descriptive in nature and employed qualitative analysis. An interview with the head librarian was conducted to determine the status of QCPL's marketing efforts. Survey questionnaires were also administered to active library users.